A comparison study on the economic performance of conventional streetlight and solar streetlight in Batu Pahat - Liew, Pok Huai (2022)
Streetlight is an essential public service that provides a safer environment to traffic users during night-time. However, improper streetlights cause some traffic and public security problems. A comparative study developed to compare the economic performance between conventional streetlight and solar streetlight in Batu Pahat. The first objective is to identify the economic performance issues of the streetlight. Fifty previous research articles were analyzed and fourteen different economic performance issues of streetlight were identified, the top two serious issues are the high electricity consumption and high bills consumption. The second objective is to compare the economic performance of solar streetlight and conventional streetlight by case study strategy, in terms of life cycle cost and payback period. Based on the calculation result, the life cycle cost of solar streetlight is 35.85% and 36.31% cheaper than conventional streetlight in both case studies. Solar streetlight has the cost and energy payback period of 50.15 years and 1.80 years in Case Study 1, meanwhile, 22.79 years and 1.75 years in Case Study 2. The third objective is to verify the most practical types of streetlight based on the economic performance by interview strategy. A total of five experts was involved in this study, while results from interview sessions show that solar streetlight is the most practical type of streetlight based on economic performance. The findings of this study lead to a better understanding and considerable optimization of energy usage and become more cost-effective for both commercial and governmental sectors such as planners, architects, and consultants.